2016
DOI: 10.1016/j.ssmph.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Childhood family wealth and mental health in a national cohort of young adults

Abstract: Purpose Mental health is critical to young adult health, as the onset of 75% of psychiatric disorders occurs by age 24 and psychiatric disorders early in life predict later behavioral health problems. Wealth may serve as a buffer against economic stressors. Family wealth may be particularly relevant for young adults by providing them with economic resources as they make educational decisions and move towards financial and social independence. Methods We used prospectively collected data from 2060 young adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
0
25
2
Order By: Relevance
“…In line with Nock's model, life events might act both as distal and proximal risk factors for NSSI. As distal risk factors, life events can increase vulnerability to stressors through pathways such as dysregulation of the immune and stress-response systems (34,35). As proximal risk factors, Kaess and colleagues (24) found that the number of life events, specifically interpersonal events in the past six months predicted the first onset of direct selfinjurious behaviors in the following year in a sample of high school students, suggesting that life events might play a critical role in the development of self-injury.…”
Section: Introductionmentioning
confidence: 99%
“…In line with Nock's model, life events might act both as distal and proximal risk factors for NSSI. As distal risk factors, life events can increase vulnerability to stressors through pathways such as dysregulation of the immune and stress-response systems (34,35). As proximal risk factors, Kaess and colleagues (24) found that the number of life events, specifically interpersonal events in the past six months predicted the first onset of direct selfinjurious behaviors in the following year in a sample of high school students, suggesting that life events might play a critical role in the development of self-injury.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in spite of the rising burden of mental health illness at various stages of the lifecourse (Alexopoulos (2005), Ferrari et al (2013) and World Health Organization 2017)commensurately few contributions have considered the relationship between childhood socioeconomic status (SES) and mental health problems, such as depression, in late-adulthood (Smith, 2015). Indeed, while the early contributions of Power et al (2007), Gilman, Kawachi, Fitzmaurice, & Buka (2002), Gilman, Kawachi, Fitzmaurice, & Buka (2003) and Lê-Scherban, Brenner, & Schoeni (2016) consider the association between childhood SES and depression at various points of the life-course, Luo & Waite (2005) and Tani et al (2016) are some of the few contributions dealing with childhood SES and depression in late-adulthoodthe former focusing on the United States and the latter on Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that low SES in childhood may not only increase exposure to stressful events. As a distal risk factor, it might also increase vulnerability to stressors through pathways such as dysregulation of the immune and stress-response systems [ 25 , 26 ]. Moreover, stressful events might be associated with D-SIB not only as distal but also as proximal risk factors: based on the SEYLE Study, Kaess and colleagues [ 24 ] found that the number of life events in the past six months predicted the first onset of D-SIB in the following year, suggesting that interpersonal life events play a critical role in the development of D-SIB.…”
Section: Introductionmentioning
confidence: 99%